Cranial irradiation in childhood mimicking neurofibromatosis type II. Issue 6 (19th April 2017) - Bokstein, Felix; Dubov, Tom; Toledano‐Alhadef, Hagit; Bernstein‐Molho, Rinat; Constantini, Shlomi; Evans, D. Gareth; Ben‐Shachar, Shay
Abstract : Neurofibromatosis type II (NF2) is a genetic disease characterized by bilateral vestibular schwannomas (VS) and other nerve system tumors. However, such tumors may be associated with environmental, rather than a genetic, etiology. Individuals fulfilling the clinical criteria of NF2 who had been treated by head ionized irradiation at a young age were compared for disease characteristics and molecular analysis with non‐irradiated sporadic NF2 cases. In the study cohort, three of 33 sporadic adult cases fulfilling NF2 diagnostic criteria had a history of early age cranial irradiation exposure. None of the irradiated patients had bilateral VS compared with 73.3% of the non‐irradiated individuals. One of the irradiated patients had no VS, while none of the non‐irradiated NF2 cases had absence of VS. All of the irradiated individuals had brain meningiomas and thyroid tumors compared with 47% and 0%, respectively, of the non‐irradiated individuals. Molecular analyses for NF2 mutations in blood of the irradiated individuals failed to detect disease‐causing mutations. This study suggest that environmental factors may mimic NF2. Identifying such non‐genetic cases fulfilling clinical criteria of the genetic disease may be crucial for the purposes of genetic counseling and patient management.